2017
DOI: 10.1186/s13027-017-0154-5
|View full text |Cite
|
Sign up to set email alerts
|

Six years genotype distribution of Human Papillomavirus in Calabria Region, Southern Italy: a retrospective study

Abstract: BackgroundAlthough analysis of the Human papillomavirus (HPV) genotype spread in a particular area has a crucial impact on public health and prevention programmes, there is a lack of epidemiological data regarding HPV in the Calabria region of Italy. We therefore update information on HPV age/genotype distribution by retrospectively analysing a cohort of women, with and without cervical lesions, living in Calabria, who underwent HPV DNA testing; moreover, we also evaluated HPV age/genotype distribution in a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
(1 reference statement)
4
5
0
Order By: Relevance
“…As expected, the infection rates of both high and low risk viruses observed in our study are comparable to that obtained in other studies including Italian women participating in opportunistic screenings but higher than those observed among Italian women attending organized cervical cancer screening programs [ 17 , 19 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As expected, the infection rates of both high and low risk viruses observed in our study are comparable to that obtained in other studies including Italian women participating in opportunistic screenings but higher than those observed among Italian women attending organized cervical cancer screening programs [ 17 , 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…In Italy, several studies evaluating the HPV prevalence and genotype distribution have been performed among women enrolled in organized and in opportunistic screening programs [ 14 17 ]. All the studies confirmed the high prevalence of Group 1 HPV genotypes, particularly HP16, 31 and 18 in SIL and invasive cervical cancer [ 17 19 ]. However, some unclassified HPVs have been also found to be relatively common in women with normal cytology.…”
Section: Introductionsupporting
confidence: 53%
“…The results of this study reveal a 22.3% overall prevalence of HPV infection in Chongqing province. The infection rate of HPV in Chongqing province was slightly lower than that reported in a previous study in the same region (26.2%) [13], similar to that in the north of Chengdu (23.05%) [14] and Henan (22.8%) [15], noticeably higher than that in Zhejiang (13.3%) [16] and Xinjiang (14.02%) [17], but signi cantly lower than that in Harbin (36.5%) [18], Fujian (38.3%) [8] and Calabria (31%) [19]. The reason for the differences in HPV prevalence between that reported in our and a previous study [13] may be that most of the participants took part in the screening in the previous study because of the discomfort symptoms of the reproductive tract, while women recruited in our study had more understanding of HPV and wanted to put HPV screening into the routine practice.…”
Section: Discussionsupporting
confidence: 74%
“…High risk HPV infection is usually an important factor of epithelial malignant tumors, which is infected in squamous epithelium by a non-enveloped DNA virus. [8][9][10] Previous studies have indicated numerous pathogenesis of EOC, but HPV infection has been pointed out by many scholars as an necessary pathogenic factor, and PCR is usually used as its detection method. 10 Women of gender are more likely to contract HPV and the prevalence rate exceeds 80%.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] The prevalence of HPV-associated female malignant tumors has been increasing in multiple populations including the Western Europe, Australia, and United States. [8][9][10] Nonetheless, few attempts have been made to analyze a panel of prevalence, significance, prognostic, and correlations of HPV infection in ovarian cancer in a Chinese cohort, account for 1/4 of the global population. The clinic pathologic features and precise pathogenesis of HPV-related ovarian cancer in Northeast China are still unclear.…”
Section: Introductionmentioning
confidence: 99%